2014
DOI: 10.1109/tpds.2013.83
|View full text |Cite
|
Sign up to set email alerts
|

An Extensible System for Multilevel Automatic Data Partition and Mapping

Abstract: Abstract-Automatic data distribution is a key feature to obtain efficient implementations from abstract and portable parallel codes. We present a highly efficient and extensible runtime library that integrates techniques for automatic data partition and mapping. It uses a novel approach to define an abstract interface and a plug-in system to encapsulate different types of regular and irregular techniques, helping to generate codes which are independent of the exact mapping functions selected. Currently, it sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 16 publications
(19 reference statements)
0
37
0
2
Order By: Relevance
“…Hitmap also provides mechanisms for the construction of reusable communication patterns at runtime that adapt to the data partition, creating a low number of aggregated communications. This leads, for example, to a performance efficiency comparable to UPC, with a reduced programming complexity and development effort [7]. Hitmap is used as a runtime system for the Trasgo parallel programming framework [8], that offers an approach similar to PGAS languages.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Hitmap also provides mechanisms for the construction of reusable communication patterns at runtime that adapt to the data partition, creating a low number of aggregated communications. This leads, for example, to a performance efficiency comparable to UPC, with a reduced programming complexity and development effort [7]. Hitmap is used as a runtime system for the Trasgo parallel programming framework [8], that offers an approach similar to PGAS languages.…”
Section: Related Workmentioning
confidence: 99%
“…Hitmap [7] is a library for the partition, mapping, and management of hierarchically distributed data structures at runtime. It was originally designed for dense arrays, and has been also extended to support sparse data structures, such as sparse matrices or graphs, using the same methodology and interface [6].…”
Section: Hitmapmentioning
confidence: 99%
See 1 more Smart Citation
“…These models do not promote the different parallelism and optimization techniques needed when processes and threads are hierarchically deployed in a hybrid environment. Comparing with UPC [3], it has been shown that Hitmap reduces the programming complexity and the memory footprint, while obtaining similar efficiency [1]. Another example of PGAS is Chapel, that proposes an interface to add mapping modules to the system [4].…”
Section: Related Workmentioning
confidence: 99%
“…Our approach is built upon the Hitmap library [1]. Hitmap reduces code development effort performing highly-efficient data distributions and aggregated communications, expressed in an abstract form.…”
Section: Introductionmentioning
confidence: 99%